2020
DOI: 10.5114/ada.2018.79445
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic manifestations of atopic dermatitis

Abstract: Atopic dermatitis is a chronic condition of complex etiology, whose clinical course involves remission and recurrence. It is not an isolated disease entity affecting only the skin, but one that co-occurs with disorders of other organs. Numerous literature reports have long confirmed the relationship between the disorder and a growing number of ophthalmic manifestations such as keratoconus and retinal detachment. Further studies are required to establish the cause of correlations and to allow for implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 59 publications
3
22
0
4
Order By: Relevance
“…This is supported by the frequent involvement of the temporal retina in atopic RD and is thought to be due to the directional forces applied during eye rubbing. Our cohort of patients also demonstrated the characteristic features of AD-associated RRD, which has a predilection for temporal retinal quadrant involvement and high concurrent rates of GRT [19,21,22], proliferative vitreoretinopathy [19,21,22], and bilateral cataract [2,22]. However, Choi et al [11] found a consistent and robust association between RRD and AD even after excluding cataract surgery from the analysis.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…This is supported by the frequent involvement of the temporal retina in atopic RD and is thought to be due to the directional forces applied during eye rubbing. Our cohort of patients also demonstrated the characteristic features of AD-associated RRD, which has a predilection for temporal retinal quadrant involvement and high concurrent rates of GRT [19,21,22], proliferative vitreoretinopathy [19,21,22], and bilateral cataract [2,22]. However, Choi et al [11] found a consistent and robust association between RRD and AD even after excluding cataract surgery from the analysis.…”
Section: Discussionsupporting
confidence: 54%
“…AD-related cataract and RRD have been reported in the literature, but their etiology and mechanism remain unspecified. There are many theories regarding the underlying cause of RRD and cataract in AD, but self-inflicted mechanical trauma through repetitive eye rubbing or slapping has gained popularity in recent years [2,12,19,20]. This is supported by the frequent involvement of the temporal retina in atopic RD and is thought to be due to the directional forces applied during eye rubbing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations